Beyond boundaries: fostering women entrepreneurs’ success through culture, family, and entrepreneurship - Kurniawan,; Pahrijal, Rival; Maulana, Agung; Maminirina Fenitra, Rakotoarisoa; Budiman, Dana; Supriandi, (Frontiers in Sociology, 2025)
IntroductionThis study investigates how social capital, family support, culture, entrepreneurial qualities, and self-efficacy influence women’s work-life balance and entrepreneurial success in Indonesia.MethodsThis research employs a quantitative methodology, gathering data via a survey with 350 participants.ResultsThe investigation findings indicate that culture, family support, and entrepreneurial tendencies significantly influence self-efficacy, social capital, and business success. Additionally, social capital and self-efficacy significantly mediate the association between the independent variables and satisfaction with work-life balance and company performance.DiscussionThe research emphasizes the significance of the interaction between social, cultural, and personal aspects in boosting entrepreneurial success and well-being, and the results offer useful insights to assist the growth of women entrepreneurs in Indonesia.